A dinâmica da competências coletivas entre grupos de trabalho: o caso da parada geral de manutenção da Copesul - Klein, Maria Josefina (Universidade do Vale do Rio do Sinos, 2008)
The market, in the last decades, is imposing to the enterprises crescent levels of complexity and interdependence not only inter-organizations but also intra-organizational. In that context, it is noticed the importance of the construction of a collective logic for the development of the competences, once the organizational tendencies are not uniform. The excellence of those collective processes can unchain collective competences, which are presented in the most varied ways, contributing to the organizational competitiveness. Thus, this dissertation has as purpose to contribute to the understanding of the collective competences that occurs starting from a strategic process that involves the mobilization of different work groups for the accomplishment of the turnaround maintenance in a company of the petrochemical sector. It is a qualitative research, of descriptive and exploratory nature, developed through the case study method in Copesul. The data were collected through semi-structured interviews, focus grou
Keywords: complementaridade; grupos de trabalho; inter-grupos; níveis de complexidade; competência coletiva; complementarity; complexity levels; inter-groups; relationships; work groups; collective competence; Ciências Sociais Aplicadas